Implementation of the Internal Quality Assurance Process: Quality Mapping Analysis at State Senior High School in Tomohon City, North Sulawesi, Indonesia - Deisy Sampul; Benny B. Binilang; J.F. Senduk; F.J.A. Oentoe (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
The Internal Quality Assurance System (IQAS) has an important position in ensuring the quality of education of each education unit. A good internal quality assurance process will guarantee the quality of education is maintained and will make it easier for schools to conduct quality mapping, preparing quality plans, fulfilling quality, evaluating and determining quality standards. The purpose of this study is to describe the implementation internal quality assurance processes at SMAN (State Senior High School) in the City of Tomohon, North Sulawesi based on quality report. This research was designed using qualitative descriptive research with the data collection techniques include observation and documentation as well as data sourced from the Quality Report online application. The results of this study indicate that the internal quality assurance process at SMAN in Tomohon City has been carried out in accordance with national education standards. The educational quality achievement still needs to be improved so that there is consistency in fulfilling quality. In addition, a culture of quality and cooperation must be fostered in order to support the internal quality assurance process. Likewise in the internal quality assurance process that requires support from various elements in the school, government and community environment.